2010
DOI: 10.1007/s11060-010-0272-z
|View full text |Cite|
|
Sign up to set email alerts
|

Convection enhanced delivery of carboplatin in combination with radiotherapy for the treatment of brain tumors

Abstract: The purpose of this study was to further evaluate the therapeutic efficacy of convection enhanced delivery (CED) of carboplatin in combination with radiotherapy for treatment of the F98 rat glioma. Tumor cells were implanted stereotactically into the brains of syngeneic Fischer rats, and 13 or 17 d. later carboplatin (20 μg/10 μL) was administered by either CED over 30 min or by Alzet osmotic pumps (0.5 μg/μL/h for 168 h.) beginning at 7 d after tumor implantation. Rats were irradiated with a 15 Gy fractionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 46 publications
9
67
1
3
Order By: Relevance
“…They reported an improvement of median survival time (MeST) or even cure of glioma bearing rats when combined with radiation therapy [12][13][14][15][16][17]. Additionally, a phase I clinical trial showed that it was safe and feasible to deliver carboplatin by CED to treat glioblastoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…They reported an improvement of median survival time (MeST) or even cure of glioma bearing rats when combined with radiation therapy [12][13][14][15][16][17]. Additionally, a phase I clinical trial showed that it was safe and feasible to deliver carboplatin by CED to treat glioblastoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…Однако последующие ýксперименты, прове-денные на фотонах 6 МВ линейного ускорителя, показали практически одинаковые результаты с облучением моноýнергетическими фотонами 78,8 кýВ синхротрона [31,33,34]. На наш взгляд, обычный линейный ускоритель можно исполь-зовать в качестве источника излучения для ýтой технологии, что позволит значительно расши-рить клиническую применимость такого подхода по сравнению с синхротронной лучевой терапи-ей, которая может быть осуществлена только на очень небольшом количестве специализирован-ных облучательных установках.…”
Section: фотон-захватная терапияunclassified
“…В дальнейших исследованиях PAT-Plat рас-сматриваются ýффективные средства доставки платиносодержащих препаратов в опухоль -ме-тод CED [33,34] и фармакологические формы [39,40]. Метод CED предлагается также и для до-ставки борсодержащих препаратов для НÇТ [41,42].…”
Section: фотон-захватная терапияunclassified
See 1 more Smart Citation
“…With these initial studies, CED was established as a viable method for providing regional distribution of large molecules, such as proteins and some conventional chemotherapeutic agents, in the brain (6)(7)(8)(9). Compared with other therapies, CED minimizes systemic and CNS toxicity by local delivery of high concentrations of therapeutics directly to the brain tissue and has led to treatment applications in several cerebral disorders, including Parkinson' s (10,11), epilepsy (12), Alzheimer' s (13,14), and malignant gliomas (4,5,(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%